Design Modification and Production of a Bicycle Powered By an Internal Combustion Engine - Akpan , W.A.; Ogbonna, P.O.; Nyaudo , I.I. (Engineering And Technology Journal, 2024)
The bicycle serves many purpose .Primarily it is used for transportation. It is also used for sports and leisure. As a means of transportation, there is need to provide more human comforts. This call s for the design modification with an internal combustion engine as a secondary driver, The research was conceived, designed and a prototype produced as shown in this research work. The minimum average speed of the bicycle over five testing speeds was 23.44km/h. The results of the test is promising. It suggests that the bicycle powered by an IC engine is a viable alternative to traditional bicycles being an innovative approach that priorities local resources. Further design should be carried out to incorporate multiple gears. Commercial production of this design is advocated for Nigerian government.